Panoramic analysis of the biological function and clinical value of SLC38A2 in human cancers: a study based on pan-cancer and single-cell analysis - Liao, Mao; Rao, Yuqing; Li, Molan; Guo, Jiayang; Guo, Kun; Li, Kaiyue; Zheng, Rui; Liu, Yifan; Wang, Qianyi; Wang, Manni; Chen, Duo; Zhang, Meng; et al. (Frontiers in Genetics, 2025)
BackgroundGlutamine metabolic reprogramming is a hallmark of tumor progression and is highly correlated with poor clinical outcomes. The excessive uptake of glutamine by tumor cells is a key factor contributing to widespread invasion, metastasis, and immune suppression. SLC38A2, an amino acid transporter widely expressed on the surface of tumor cells, has not been thoroughly studied regarding its function and prognostic significance in tumor progression. Our objective is to employ bioinformatics methods to conduct a comprehensive and in-depth analysis of SLC38A2 across various cancers, aiming to elucidate its role and prognostic value in tumor biology.MethodsBy comprehensively incorporating gene expression and clinical data from the TCGA tumor database, GTEx database, Human Protein Atlas, and GEO database, we analyzed the expression profile, mutations, and established prognostic models for SLC38A2 across various cancers. Additionally, we investigated the enrichment of SLC38A2 at the single-cell level in 12 types of cancer and analyzed its temporal expression patterns in different cell subgroups in breast and pancreatic cancer. We also studied the correlation between SLC38A2 and glutathione metabolism.ResultsCompared to normal tissues, SLC38A2 exhibits significant differential expression in 15 types of cancer and serves as a prognostic risk factor in BRCA (HR = 1.597, p < 0.05), LUAD (HR = 1.650, p < 0.01), MESO (HR = 2.007, p < 0.05), and PAAD (HR = 1.761, p < 0.05), while acting as a protective factor in KIRC (HR = 0.625, p < 0.05). Furthermore, SLC38A2 is positively correlated with tumor and stromal cells, negatively correlated with immune cell infiltration, and associated with immune exhaustion. In BRCA, SLC38A2 is highly expressed during early differentiation of malignant and stromal cells, and enriched in late differentiation of immune cells. Moreover, the expression of SLC38A2 shows a general positive correlation with glutathione metabolism genes in BRCA, LUAD, MESO, and PAAD, demonstrating diagnostic value.ConclusionSLC38A2 shows widespread changes in expression patterns within tumor tissues, making it an effective diagnostic and prognostic biomarker. It is enriched in malignant cells and tumor-infiltrating stromal cells, while negatively correlated with the infiltration of many cells involved in anti-tumor immunity. Targeting SLC38A2 presents a viable therapeutic strategy by inhibiting glutamine competition and relieving immune suppression in the tumor microenvironment.